Implementasi Manajemen Strategi dalam Meningkatkan Pendapatan Rumah Sakit : Tinjauan Literatur - Frety Tiurma Ara; Khoirunnisa Siregar; Purwadhi Purwadhi; Yani Restiani Widjaja (Lembaga Pengembangan Kinerja Dosen, 2026)
The implementation of strategic management has become an important approach for hospitals to improve revenue amid an increasingly competitive healthcare environment. This study aims to examine the role of strategic management in enhancing hospital revenue through a systematic literature review. The study employed a Systematic Literature Review (SLR) method following the PRISMA 2020 guidelines. Articles were retrieved from Scopus, PubMed, Google Scholar, and Sinta databases, covering publications from 2020 to 2025. The selection process resulted in 47 articles that were analyzed thematically. The findings indicate that strategic management contributes to hospital revenue improvement through comprehensive strategic planning, consistent strategy implementation, effective resource management, and continuous performance evaluation. Hospitals that successfully align organizational strategies with operational decision-making tend to achieve more stable financial performance and greater adaptability to environmental changes. These findings highlight the importance of strategic management as a long-term managerial framework to support financial sustainability and competitiveness in hospitals.